First observations of SO2 from the satellite Suomi NPP OMPS: Widespread air pollution events over China. Issue 18 (19th September 2013) - Yang, Kai; Dickerson, Russell R.; Carn, Simon A.; Ge, Cui; Wang, Jun
Abstract : [1] Severe smog episodes over China in January 2013 received worldwide attention. This air pollution was distinguished by heavy loadings of fine particulate matter and SO2 . To characterize these episodes, we employed the Ozone Mapping and Profiler Suite, Nadir Mapper (OMPS NM), an ultraviolet (UV) spectrometer flying on the Suomi National Polar‐orbiting Partnership (SNPP) spacecraft since October 2011. We developed an advanced algorithm to quantify SO2 in the lower troposphere and achieved high‐quality retrievals from OMPS NM, which are characterized by high precision, ∼0.2 Dobson Units (DU; 1 DU = 2.69×10 16 molecules/cm 2 ) for instantaneous field of view SO2 data and low biases (within ±0.2 DU). Here we report SO2 retrievals and UV aerosol index data for these pollution events. The SO2 columns and the areas covered by high pollutant concentrations are quantified; the results reveal for the first time the full extent (an area of ∼10 6 km 2 containing up to 60 kt of SO2 ) of these episodes. Key Points: Reveal for the first time the full extent of synoptic scale pollution episodes Demonstrate monitoring global atmospheric environments with SNPP/OMPS Highlight that coal combustion contributes to air pollution today in China